62+5=4z-7

Simple and best practice solution for 62+5=4z-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 62+5=4z-7 equation:


Simplifying
62 + 5 = 4z + -7

Combine like terms: 62 + 5 = 67
67 = 4z + -7

Reorder the terms:
67 = -7 + 4z

Solving
67 = -7 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
67 + -4z = -7 + 4z + -4z

Combine like terms: 4z + -4z = 0
67 + -4z = -7 + 0
67 + -4z = -7

Add '-67' to each side of the equation.
67 + -67 + -4z = -7 + -67

Combine like terms: 67 + -67 = 0
0 + -4z = -7 + -67
-4z = -7 + -67

Combine like terms: -7 + -67 = -74
-4z = -74

Divide each side by '-4'.
z = 18.5

Simplifying
z = 18.5

See similar equations:

| 5=-4b-8 | | 3p+4p-2=12 | | -(2x-5)=2(x+2)+3x | | 2+u=4 | | -3f-1=8-3f | | 5=2y^2+2y | | 4=-8f+5 | | 6x+3x+5+7=48 | | 2/3x-14=22 | | x=2x+x^2 | | 72+5x-8+6x+6=180 | | 7a+6=-24 | | 3x-12-4x=6+5x | | 7+r=9 | | 9(x+6)+2(x+6)=7x-7 | | 9x-12y=8 | | 6(2c+10)=5(c+5) | | 4n^2-7=-7n | | 30/20=x/4 | | 5c+9=4z-1 | | 3+4(x-5)=34 | | 9(x+1)+4(x+1)=6x-6 | | -6+11=-5-2 | | x^7-6x^5+2x^4-5=0 | | 2p-3=11 | | 3+7n=1+6n | | ln^3x=5 | | 5k^2=6-k | | (x+1)+(y-2)=7 | | 4x+25=8x+37 | | 16-2w=5w+9 | | 8x=215-13x |

Equations solver categories